THE PREVALENCE OF THE MONTREAL CONVENTION AFTER THE 2017 STF DECISION; WHAT ABOUT JURISDICTION? - Defossez, Delphine; Carrasco , Janny (Direito.UnB - Revista de Direito da Universidade de Brasília, 2021)
This article analyses the possible impacts of the 2017 Brazilian Supreme Federal Court (STF) decision, which put an end to the long-standing dispute regarding the prevalence of the Montreal Convention over the Código de Proteção e Defesa do Consumidor (CDC), on jurisdiction. Indeed, the Montreal Convention contains an article regulating jurisdiction in case of both delays (Article 33(1)) and death or bodily injury (Article 33(2)). This provision is mostly in line with Article 21 of the Novo Código de Processo Civil (CPC). However, in some situations a conflict might occur. The article first analyses the decision and then the conflicts between Article 33 Montreal and Article 21 CPC. It then looks at various interpretations of Article 33 around the world and the concept of forum non conveniens. It concludes that the conflicts might only be present in theory, as some interpretations of Article 33 would be in line with the manner Brazilian courts already decide cases.